2020
DOI: 10.3390/land9110430
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Changes in a Viewshed in the Western Carpathians Landscape as a Result of Reforestation

Abstract: A viewshed analysis is of great importance in mountainous areas characterized by high landscape values. The aim of this research was to determine the impact of reforestation occurring on former pasturelands on changes in the viewshed, and to quantify changes in the surface of glades. We combine a horizontal and a vertical approach to landscape analysis. The changes in non-forest areas and the viewshed from viewpoints located in glades were calculated using historical cartographic materials and a more recent Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In the general climate of abandonment that rural and mountainous areas have been undergoing in the past decades, not limited to the Apennines, but well-documented especially in Eastern Europe [88][89][90], it is thus imperative to look to these traditions and to involve the people who are custodians of ecological knowledge in order to safeguard both biological and cultural diversity. Well-preserved landscapes would also have a positive effect on tourism in these areas, as it has been shown that managed grasslands are more attractive and have better visibility than abandoned landscapes [61,91]. This type of pastoralism is kept alive by the cultural traditions tied to it, more so than by some type of economic benefit, even though areas with more widespread agrienvironmental schemes are less likely to be abandoned [90].…”
Section: Discussionmentioning
confidence: 99%
“…In the general climate of abandonment that rural and mountainous areas have been undergoing in the past decades, not limited to the Apennines, but well-documented especially in Eastern Europe [88][89][90], it is thus imperative to look to these traditions and to involve the people who are custodians of ecological knowledge in order to safeguard both biological and cultural diversity. Well-preserved landscapes would also have a positive effect on tourism in these areas, as it has been shown that managed grasslands are more attractive and have better visibility than abandoned landscapes [61,91]. This type of pastoralism is kept alive by the cultural traditions tied to it, more so than by some type of economic benefit, even though areas with more widespread agrienvironmental schemes are less likely to be abandoned [90].…”
Section: Discussionmentioning
confidence: 99%
“…In a relatively diverse landscape, this detail seems to be sufficient, although it is still difficult to find works with such accuracy, especially for Poland [52]. Moreover, since the computation (1996), much effort has been put in by later works to develop faster and more efficient GIS tools related to view line tracking and zooming, reference plane analysis, and view partitioning into blocks [53][54][55][56]. For example, Miller and Law [57] performed an interesting analysis of view structure by building a 3D terrain model and calculating visibility shares of specific land cover types according to Corine Land Cover.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, its internal value should be assessed regularly. The direction and dynamics of landscape changes could be different in particular parts of the mountains [59].…”
Section: Discussionmentioning
confidence: 99%